Modification of the Paediatric Gastro-oesophageal Reflux Disease Symptom and Quality of Life Questionnaire (PGSQ) for children with cerebral palsy: a preliminary study - Mark Tighe; Catherine Tuffrey; Sarah Mills; Lee Tbaily (BMJ Publishing Group, 2024)
Objective Gastro-oesophageal reflux disease (GORD) is a common condition affecting children, characterised by the passage of gastric contents into the oesophagus causing pain, vomiting and regurgitation. Children with neurodisability (such as cerebral palsy; CP) are predisposed to more severe GORD due to coexisting gut dysmotility and exclusive/supplementary liquid diet; however, there are no existing tools or outcome measures to assess the severity of GORD in this patient group. For children without CP, the 'Paediatric Gastro-oesophageal Symptom and Quality of Life Questionnaire' (PGSQ) assesses symptoms and response to treatment, but the questions are not suitable for children with significant cognitive impairment. We aimed to adapt the existing PGSQ assessment tool to enable use in evaluating children with CP and GORD.Patients/interventions Cognitive interviews were conducted by the research team with six parents/carers of children (aged 3-15) with CP (Gross Motor Function Classification System level V) who have current or past symptoms of reflux. They were asked to interpret the questionnaire using a 'think-aloud technique,' and offer suggestions on alterations to questions. Reasons for changing questions included confusing/difficult to understand questions, differing interpretations of questions and response choices not applying to the patient group.Results The PGSQ was modified iteratively following each interview. Overall, parents/carers reported that it was acceptable to recall information over the past 7 days. In the final version, it was felt the questions were relevant, useful and related to symptoms that they observed. It was easy to comprehend with no uncomfortable questions. Suggestions for future work included a section specifically focusing on the school day answered by school staff and home life answered by carers who assist them in the home.Conclusions We have adapted the PGSQ to improve relevance and acceptability for families/carers of children with symptoms of GORD and neurodisability. Further work is needed to validate the questionnaire for this patient group.